Catalytic Methods in Flow Chemistry - Len, Christophe (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The chemical industry is essential in the daily humn life of modern society; despite the misconception about the real need for chemical production, everyone enjoys the benefit of the chemical progress. However, the chemical industry generates a large variety of products, including (i) basic chemicals, e.g., polymers, petrochemicals, and basic inorganics; (ii) specialty chemicals for crop protection, paints, inks, colorants, textiles, paper, and engineering; and (iii) consumer chemicals, including detergents, soaps, etc. For these reasons, chemists in both acdemia and industry are challenged with developing green and sustainable chemical production towrad the full-recycling of feedstocks and waste. Aiming to improve the intensification of the process, chemists have established chemical reactions based on catalysis, as well as alternative technologies, such as continuous flow. The aim of this book is to cover promising recent research and novel trends in the field of novel catalytic reactions (homogeneous, heterogeneous, and enzymatic, as well as their combinations) in continuous flow conditions. A collection of recent contribution for conversion of starting material originated from petroleum resources or biomass into highly-added value chemicals are reported.